Latin America after Mexico : quickening the pace - Burki, Shahid Javed, 1938- 14.09.1938- (World Bank Latin American and Caribbean studies, 1996)
"Analyzes Mexico's Dec. 1994 currency devaluation and impact of resulting crisis on other countries in the region. Contends that crisis acted as a 'wake-up call,' prompting many countries to implement policy reforms"--Handbook of Latin American Studies, v. 57